Ten-year summary of K.S.I.A. swine testing station data - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Swine testing stations "performance prove” breeding lines for genetic progress in the swine industry. The phenotype of a boar is a combination of his genetic ability and environment (nutrition, health, and etc.). Thus by using central test stations where all pigs are housed in similar pens and fed the same rations, the effect of environment is reduced so the genetic ability is more accurately appraised. The Kansas Swine Testing Station first tested hogs for Kansas Breeders the fall of 1958. Since then about 100 breeders have participated in the test station.
Swine Industry Day 1969 is known as Swine Day, 1969
Keywords: Swine; Performance; Swine testing stations